2020
DOI: 10.13189/saj.2020.080610
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Natural Apophyseal Glides versus Positional Release Therapy in the Treatment of Chronic Mechanical Neck Dysfunction

Abstract: Background: Mechanical neck dysfunction (MND) is a common disorder prevailing among the individuals of different populations. It is characterized by pain and limited range of motion (ROM) which, in turn, affects the activities of daily living and quality of life. Although manual therapy is commonly used in MND treatment to restore a range of motion and reduce pain, some techniques have low evidence in treating MND. Aim: This study was conducted to compare the effect of sustained natural apophyseal glides (SNAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies reported that cervical stabilization exercises can control FHP [6]. Stretching can increase muscle flexibility [31]. However, in between-group comparison, there was a significant difference between CVA and CRA.…”
Section: Thoracic Spine Extension Exercisesmentioning
confidence: 84%
“…Previous studies reported that cervical stabilization exercises can control FHP [6]. Stretching can increase muscle flexibility [31]. However, in between-group comparison, there was a significant difference between CVA and CRA.…”
Section: Thoracic Spine Extension Exercisesmentioning
confidence: 84%
“…Mechanical cervical dysfunction is a common disorder in other populations, resulting a pain and limited range of motion (ROM) negatively affect everyday life, activities and quality of life [12]. Poor spinal postures that can affect scapular alignment, movements, muscle activity include forward head posture (FHP) [13] and excessive thoracic kyphosis in the back [10][11], [14].…”
Section: Introductionmentioning
confidence: 99%